Effect of Kangaroo Treatment Method on Temperature Body in Low Birth Weight Infants - Ni Komang Ayu Resiyanthi; Ni Kadek Sulasih; A.A Istri Dalem Hana Yundari (Indonesian Journal of Global Health Research, 2021)
The prevalence of LBW in Indonesia is 6.2% of 47,011 births, while in Bali Province LBW is 5.6% of 786 births (Riskesdas, 2018). Data shows that more than 20 million babies worldwide are estimated to be born with LBW. Hypothermia is the most common problem found in babies with LBW, so nursing actions are needed that can overcome the problem of hypothermia in LBW. Kangaroo Mother Care (KMC) is one of the nursing actions that can be attempted to overcome this hypothermic problem. The purpose of this study was to determine the effect of the Kangaroo Mother Care (KMC) method on temperature stability in Low Birth Weight (LBW) infants in the Perinatology Room of the Gianyar Regional General Hospital. This type of research is pre experimental design with one-group pre-post test design. Sampling using quota sampling technique with a sample size of 17 babies. Samples were selected based on inclusion and exclusion criteria, where one of the inclusion criteria was LBW who did not have congenital abnormalities, babies who had reflexes and had good coordination of suction and swallowing. After the sample is selected, then a pretest is carried out by measuring the baby's body temperature, then the mother of the baby is taught about KMC for 15 minutes and then asked to repeat independently for 60 minutes, and after that do a posttest, namely measuring the temperature after giving the KMC method. Analysis of the effect of Kangaroo Mother Care (KMC) on the temperature stability of infants using the statistical test paired t-test results obtained p value = 0.000 so that p value <0.05. This shows that there is an effect of the Kangaroo Mother Care (KMC) method on temperature stability in LBW babies in the Perinatology Room of the Gianyar Regional General Hospital.